Autoimmune hepatitis:- Another specific immune marker - Al- obeidy, Eman , sh.; Mousawy, Khailda M.; Hasso, Maan G.; Fayadh, Makki H.; AL-Khalid, Nawal M. (Journal of the Faculty of Medicine Baghdad, 2006)
Background: